Ketahanan Ubi Jalar terhadap Penyakit Kudis - Eko Agus Martanto; Haryono Semangun; Christanti Sumardiyono (Jurnal Perlindungan Tanaman Indonesia, 1997)
The experiment was conducted to know the resistance of sweet potato cultivars to scab caused by Elsinoe batatas, the incubation period, and the influence of stomatal density to the resistance of the host. The test showed that Malothok, Mlg 12538, and Prambanan cultivars were moderately resistant, while Ciceh-5 was resistant. The incubation period on Ciceh-5 was longer than that on the other moderately resistant cultivars. On resistant cultivar, stomatal density was lower than that on moderately resistant cultivars.